2022
DOI: 10.1177/14648849211073450
|View full text |Cite
|
Sign up to set email alerts
|

Of essential workers and working from home: Journalistic discourses and the precarities of a pandemic economy

Abstract: This article considers how reporting about work during the COVID-19 pandemic operated as a field of discourse that challenged the ideological workings of neoliberalism. By documented the risks and stresses workers of all classes faced during the pandemic, the reporting began to question neoliberal capitalism as socially unsustainable. Drawing on a corpus of 151 long-from articles and commentary, we show how journalistic discourse structured relationships between different classes of workers and implicated inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This finding is consistent with other research that has identified a media focus on critical healthcare roles during the pandemic ( Kyriakidou et al., 2021 ; Musheno et al., 2021 ). Such findings provide a counterpoint to arguments that the pandemic led to a greater awareness of the critical nature of ‘low-skilled’ labour such as cleaning and retail jobs, and the difficulties faced by workers in these roles ( Musheno et al., 2021 ; Creech et al., 2022 ). Paul et al.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This finding is consistent with other research that has identified a media focus on critical healthcare roles during the pandemic ( Kyriakidou et al., 2021 ; Musheno et al., 2021 ). Such findings provide a counterpoint to arguments that the pandemic led to a greater awareness of the critical nature of ‘low-skilled’ labour such as cleaning and retail jobs, and the difficulties faced by workers in these roles ( Musheno et al., 2021 ; Creech et al., 2022 ). Paul et al.…”
Section: Discussionmentioning
confidence: 71%
“…(2021) argue that COVID-19 opened up “more expansive portrayals of who is on the frontlines and what it means to be engaged in this work” (2021, 34), with migrant workers and workers from ethnic minority groups foregrounded. Similarly, an analysis of 151 articles published in national newspapers in the US found that essential workers in low-wage jobs were valorised as keeping society running, and often contrasted against the experiences of professionals working from home ( Creech et al., 2022 ). Such research might suggest that a corpus analysis of ‘frontline’ during the COVID-19 pandemic would reveal an increase in the number or type of occupations associated with the word ‘frontline’ during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic shows how journalists are increasingly individualized and vulnerable in an increasingly atomized industry (Creech & Maddox, 2022;Waisbord, 2019). In recent years, various works of literature have begun to place employment issues in journalism in the discourse on precarization, which is getting stronger.…”
Section: Introductionmentioning
confidence: 99%